The role of image-guided therapy in the management of colorectal cancer metastatic disease. (April 2017) - de Baere, Thierry; Tselikas, Lambros; Yevich, Steven; Boige, Valérie; Deschamps, Frederic; Ducreux, Michel; Goere, Diane; Nguyen, France; Malka, David
Abstract: The European Society for Medical Oncology (ESMO) have stressed that the option for treating oligometastatic disease is a strategy of local ablative therapy, the goal of which is to improve disease control. The spectrum of the local ablative therapy toolbox described by the ESMO includes surgical R0 resection, percutaneous ablation and intra-arterial therapies, the choice of treatment being left to the multidisciplinary team. Interventional therapy involving image-guided treatment offers the possibility of less invasive treatments for colorectal cancer metastases in the liver, lung and bone by preserving from toxicity distant healthy organs or even parts of the diseased organs. Oligometastases can be targeted by image-guided puncture for percutaneous ablation by delivering locally, through inserted probes, heat (radiofrequency, microwaves), extreme cold (cryoablation) or electric pulses (electroporation). Radiofrequency (RFA) is the mainstay of percutaneous ablation and provides local control rates of around 90% when metastases are small (<3 cm), located away from hilum and large vessels, and perfectly visible under imaging guidance. The lung provides a specific environment with excellent visibility of the target tumour, and insulation of the tumour by the healthy lung improves thermal delivery. RFA of colorectal lung metastases provides a 5-year overall survival of 56.0%, with a 91.6% control rate for metastases with a diameter <3 cm. These results are comparable to results of surgical series. Non-resectable, non-ablatable liver metastases can be targeted through their preferential arterial vascularisation with hepatic arterial infusion chemotherapy (HAIC) or selective internal radiation therapy (SIRT) with radioactive microspheres. HAIC with oxaliplatin has demonstrated an impressive response rate when patients who have previously failed intravenous oxaliplatin are rechallenged. The response rate in first-line therapy is around 90%, with conversion to surgery in roughly 40% of patients. SIRT has recently demonstrated a benefit for progression-free survival in the liver when used as first-line treatment in combination with systemic therapy.